Konstruksi Pengukuran Kinerja Social Enterprise Berbasis Perspektif Deep Ecology - Diana Nurindrasari; Ardiansyah Ardiansyah (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
Social Enterprises has been an explosion in methodologies and tools for assessing social performance and impact, but with little systematic analysis and comparison across different approaches. Social Enterprises need to start systemically measuring their performances to support decision-making and ensure the development and sustainability of the environment and society. This paper aims to contribute to the state-of-the-art literature by developing an approach that could be applied by Social Enterprises to measure their results concerning social, environmental, and economic impacts. By embracing interdisciplinary views of accounting and anthropology, we use synchronic-diachronic literature study. This research using deep ecology to construct multidimensional perspective in building the foundation of performance measurement on Social Enterprises.